Design and Implementation of an Additively Manufactured Reactor Concept for the Catalytic Methanation - Hauser, Alexander; Neubert, Michael; Feldner, Alexander; Horn, Alexander; Grimm, Fabian; Karl, Jürgen (Applied Sciences, 2022)
The methanation process is discussed as one way to chemically store renewable energy in a future energy system. An important criterion for its application is the availability of compact, low-cost reactor concepts with high conversion rates for decentralized use where the renewable energy is produced. Current research focuses on the maximization of the methane yield through improved temperature control of the exothermic reaction, which attempts to avoid both kinetic and thermodynamic limitations. In this context, traditional manufacturing methods limit the design options of the reactor and thus the temperature control possibilities. The use of additive manufacturing methods removes this restriction and creates new freedom in the design process. This paper formulates the requirements for a novel methanation reactor and presents their implementation to a highly innovative reactor concept called ‘ADDmeth’. By using a conical reaction channel expanding from Ø 8 to 32 mm, three twisted, expanding heat pipes (Ø 8 mm in evaporation zone, Ø 12 mm in condenser zone) and a lattice structure for feed gas preheating and mechanical stabilization of the reactor, the design explicitly exploits the advantages of additive manufacturing. The reactor is very compact with a specific mass of 0.36 kg/kW and has a high share of functional volume of 52%. The reactor development was accompanied by tensile tests of additively manufactured samples with the used material 1.4404 (316 L), strength calculations for stability verification and feasibility studies on the printability of fine structures. Ultimate tensile strengths of up to 750 N/mm2 (at room temperature) and sufficiently high safety factors of the pressure-loaded structures against yielding were determined. Finally, the paper presents the manufactured bench-scale reactor ADDmeth1 and its implementation.
CRIS-Team Scopus Importer:2022-10-07
Keywords: additive manufacturing; catalytic methanation; conic reaction channel; heat pipes; reactor design

Direct catalytic methanation of Biogas (DMB): From laboratory experiments to demonstration scale - Markthaler, Simon; Grimm, Fabian; Karl, Jürgen (4th Doctoral Colloquium BIOENERGY, 2021)

Experimentelle Untersuchung zur Katalysatordeaktivierung und zur Leistungsfähigkeit eines zweistufigen Methanisierungssystems für die Dirketmethanisierung von Biogas - Markthaler, Simon; Grimm, Fabian; Karl, Jürgen (10. Statuskonferenz BMWi-Forschungsnetzwerk Bioenergie, 2021)

Impact of syngas from biomass gasification on solid oxide fuel cells: A review study for the energy transition - Li, Yixing; Pang, Yin; Tu, Hengyong; Torrigino, Federica; Biollaz, Serge M. A.; Li, Zhuo; Huang, Yanqin; Yin, Xiuli; Grimm, Fabian; Karl, Jürgen (Energy Conversion and Management, 2021)
Operating solid oxide fuel cells (SOFC) with gas from biomass gasification ensures a combined heat and power system with a less complex gas cleaning and an efficient use of biogenic resources. The main challenge and obstacle for the application of SOFCs with bio-syngas is the degradation of Nickel anode caused by carbon deposition, Nickel re-oxidation and contaminants such as tar and sulfur. Understanding the degradation mechanisms, identifying the optimal operation conditions and developing advanced SOFC materials, regeneration methods and diagnosis tools are essential for a stable, efficient and eco-friendly system. This work reviews the current development in terms of the deterioration of cell anodes, the underlying materials sciences, operation of coupled system, the economic feasibility and further approaches of efficiency elevation.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Biomass gasification; Degradation; Heat pipe; Integrated biomass gasification fuel cell systems; Solid oxide fuel cell (SOFC); Tar

In-situ electrochemical impedance analysis of a commercial SOFC stack fueled by real wood gas - Torrigino, Federica; Grimm, Fabian; Karl, Jürgen; Herkendell, Katharina (Heliyon, 2024)
The combination of solid oxide fuel cells (SOFCs) and wood gasification has the potential to significantly increase renewable electricity production and decrease emissions. Depending on the quality of the wood gas, degradation processes have a significant impact on the reliability and lifetime of the SOFC. Using electrochemical impedance spectroscopy (EIS) and subsequent distribution of relaxation times (DRT) analysis, the impact on the degradation of coupling wood gasification with a commercial SOFC stack is determined in this study. The thermal behavior of the SOFC stack under various operating conditions, as well as various synthetic wood gas mixtures classified by their hydrogen-to-carbon (H/C) ratio, was assessed. The decrease in the H/C ratio from 8 to 1, observed during syngas and real wood gas operation, leads to a rightward shift in the Nyquist plots, suggesting an increase in the SOFC stack's impedance. Correlations between variations in the H/C ratio and their effects on anodic electrooxidation, ionic conduction, gas transport, and diffusion were identified using DRT analysis to interpret the EIS results. By incorporating an upstream desulfurization system and ensuring an H/C ratio greater than 2, the coupling of biomass gasification with the SOFC stack was stable to degradation issues.
CRIS-Team Scopus Importer:2024-06-14
Keywords: Biomass; Distributed power generation; Distribution of relaxation times (DRT); Electrochemical impedance spectroscopy (EIS); Solid oxide fuel cell (SOFC); Wood gas

Numerical and experimental analysis of the effects of tar components on single planar SOFC under high fuel utilization - Li, Yixing; Grimm, Fabian; Karl, Jürgen (Electrochimica Acta, 2023)
One of the main challenges and obstacles for the application of SOFCs with wood gas is the degradation of Nickel anode caused by heavier hydrocarbons from the gasification process. The unclear conversion process on the anode and the fluctuant content of tars in wood gas will cause problems like the excess of critical fuel cell utilization and thus the oxidation of Nickel anode. This work focuses on the experimental and numerical analysis of tar conversion on the single SOFC under different conditions. A three-dimensional Computational Fluid Dynamics (CFD) model for an electrolyte-supported single cell was developed using the commercial CFD code FLUENT. The conversion kinetics of tar is validated by experimental results and implemented into the model. With this model, local distributions of Nernst voltage across the anode area are demonstrated. Areas, where an oxidation of Nickel is to be feared, are identified. Both experimental and simulative results have proved the positive effect of toluene reforming on preventing Ni from re-oxidation.
CRIS-Team Scopus Importer:2023-03-31
Keywords: CFD; Fuel utilization; Reforming; Solid oxide fuel cell (SOFC); Tar

The conversion of naphthalene on SOFC anodes and its impact on the cell performance - Li, Yixing; Grimm, Fabian; Karl, Jürgen (Fuel, 2023)
The operation of a SOFC with biomass-derived syngas would provide convincing solutions for combined heat and power production from renewable sources. In principle, the tar components in the wood gas can be reformed on Ni-based SOFC anodes, hence, giving access to additional hydrogen as fuel. The investigation of the kinetic-limited conversion process on anodes and its effect on the electrochemical processes of the SOFC is yet still insufficient. This paper presents the experimental study of the conversion of naphthalene on a single planar electrolyte-supported cell with varying temperature and naphthalene concentration. Thereby the impact of the incomplete conversion of naphthalene on open circuit voltage, methane conversion and cell performance is investigated. A 1-D kinetic model reveals the correlation between the slow naphthalene reforming and the open circuit voltage. The adsorption of naphthalene on the Ni catalyst not only impedes the reforming of methane, but also slows down the kinetics of electrochemical reaction. However, the produced hydrogen from steam reforming reaction is still beneficial in terms of preventing Ni re-oxidation under higher fuel utilization in H2 gas mixture.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Degradation; Fuel utilization; Naphthalene; Solid oxide fuel cell (SOFC); Tar

The impact of tar contaminants on SOFC performance under high fuel utilization condition - Li, Yixing; Grimm, Fabian; Neubert, Michael; Treiber, Peter; Karl, Jürgen (Jahrestreffender ProcessNet-FachgruppeEnergieverfahrenstechnik, 2021)

Utilization of Synthetic Steel Gases in an Additively Manufactured Reactor for Catalytic Methanation - Hauser, Alexander; Feldner, Alexander; Treiber, Peter; Grimm, Fabian; Karl, Jürgen (Sustainability, 2023)
The path to European climate neutrality by 2050 will require comprehensive changes in all areas of life. For large industries such as steelworks, this results in the need for climate-friendly technologies. However, the age structure of existing steelworks makes transitional solutions such as carbon capture, utilization and storage (CCUS) necessary as short-term measures. Hence, a purposeful option is the integration of technical syntheses such as methanation into the overall process. This work summarizes hydrogen-intensified methanation experiments with synthetic steel gases in the novel additively manufactured reactor ‘ADDmeth1’. The studies include steady-state operating points at various reactor loads. Blast furnace gas (BFG), basic oxygen furnace gas (BOFG) and three mixtures of these two gases serve as carbon sources. The methanation achieved methane yields of 93.5% for BFG and 95.0% for BOFG in the one-stage once-through setup. The results suggest a kinetic limitation in the case of BFG methanation, while an equilibrium limitation is likely for BOFG. There is a smooth transition in all respects between the two extreme cases. The reaction channel inlet temperature (Formula presented.) showed a large influence on the reactor ignition behavior. By falling below the threshold value, a blow-off occurred during experimental operation. By means of a simulation model, practical operating maps were created which characterize permissible operating ranges for (Formula presented.) as a function of the gas composition and the reactor load.
CRIS-Team Scopus Importer:2023-05-26
Keywords: BFG; BOFG; by-product gas; catalytic methanation; ignition behavior; simulation; temperature profiles

Utilization of wood gas in SOFC stacks - Torrigino, Federica; Grimm, Fabian; Karl, Jürgen (11th Energy Colloquium of the Munich School of Engineering, 2021)